2008
DOI: 10.1590/s1678-77572008000500005
|View full text |Cite
|
Sign up to set email alerts
|

Fracture strength of different soldered and welded orthodontic joining configurations with and without filling material

Abstract: The aim of this study was to compare the mechanical strength of different joints made by conventional brazing, TIG and laser welding with and without filling material. Five standardized joining configurations of orthodontic wire in spring hard quality were used: round, cross, 3 mm length, 9 mm length and 7 mm to orthodontic band. The joints were made by five different methods: brazing, tungsten inert gas (TIG) and laser welding with and without filling material. For the original orthodontic wire and for each k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
(39 reference statements)
0
13
0
2
Order By: Relevance
“…There are studies 9,13-18-26 combination, but few study 9,13 is about orthodontic band-wire combination. Band-wire combinations are commonly used during fabricating the active or anchorage orthodontic appliances so that the mechanical behavior researches of this combination are necessary and important.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are studies 9,13-18-26 combination, but few study 9,13 is about orthodontic band-wire combination. Band-wire combinations are commonly used during fabricating the active or anchorage orthodontic appliances so that the mechanical behavior researches of this combination are necessary and important.…”
Section: Discussionmentioning
confidence: 99%
“…There are different results in the literature based on the influence of brazing or welding on tensile strength. When band to wire joints were evaluated; Bock et al 9 demonstrated that the mean values of fracture strength did not differ significantly between laser welding with filling material (441.3 N) and brazing (406.7 N), but a slight tendency to lower means in laser welding without filling material (328.8 N). In a different study, Bock et al 22 showed no significant differences between the mean fracture loads for the band-to-wire joints between laser welding (354.4 N) and brazing (406.6 N), although there was less variability with the laser welding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantages of laser welding systems can be summarized as follows: no solder and thus no galvanic corrosion at the joint. Some phenomena can be blurred by using protection inert gases in the area of the joint(Jens Johannes Bock, 2008;Szuhanek, 2006). The application of laser welding technology allows titanium to be welded predictably and precisely in order to achieve an accurate fit of a milled framework.…”
Section: Fig 1 Welded Orthodontic Constructive Solutionsmentioning
confidence: 99%